Real time counting audience system in football stadium - Abdul Rahman Kram
This report is about to explore how different motion detectors operate, to gain the knowledge how to construct transmitter and receiver detector circuit, to develop real time counting audience system, to improve security system procedure for entrance football stadium and to solve the sale fake ticket from bloom and deceptive the buyer